AminoViewer: Supporting Biochemistry Education with Augmented Reality - Machado, Liliane; Alves, Alan; Felipe, Cícero (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227696, 2022)
AminoViewer is a didactic material, which uses the association of a booklet and an application (AminoViewer3D), to establish knowledge about the structure and function of amino acids, a subject covered in biochemistry disciplines in university courses. The booklet presents the 20 common amino acids, their two-dimensional structures, their chemical characteristics, their biological functions and their structural formula. For each amino acid, an image of its structural formula is presented. Using the AminoViewer3D application, each of the images leads to a three-dimensional visualization of the molecules, using augmented reality technology. With the use of augmented reality, the student can manipulate the molecule three-dimensionally, exploring its characteristics.